Orderings a class of unicyclic graphs with respect to Hosoya and Merrifield-Simmons Index - Wang, Yan-Feng; Ma, Ning (Universiti Kebangsaan Malaysia, 2016)
Hosoya and Merrifield-Simmons index were the two valuable topological indices in chemical graph theory. The Hosoya and Merrifield-Simmons index of the class of unicyclic graphs G(k) were investigated, according to the distance between u and v on Cm, their orderings with respect to these two topological indices were obtained.